Scrivere il corpo, ferire il testo: la rappresentazione della violenza nel romanzo La sangre de la aurora (2013) (Altre Modernità, 2020)
In the 1980 began the internal conflict in Peru between the armed forces, the Peruvian Communist Party-Shining Path (PCP-SL) and the Túpac Amaru Revolutionary Movement (MRTA). The civil war lasted twenty years and it caused nearly 70.000 deaths. The novel Blood of the Dawn (2013) by Claudia Salazar Jiménez was awarded the Las Americas Narrative Prize of Novel in 2014 due to its originality among the abundant literature on this difficult and polemic episode of the recent history of Peru. The fiction is about three women’s lives during the internal conflict, but given that the violence can’t be told by words, Claudia Salazar let women bodies talk and represents the tragedy of “the time of fear” by them. The way their bodies became a symbol of the war and the useless violence turns the novel into a biosemiotics system of representation. In this sense Claudia Salazar’s debut novel exceeds from what is considered the canon of the internal conflict narrative.